The Toyota Way or the unions' way?: Examining the nexus between lean and unions in Toyota Australia. Issue 6 (26th March 2021) - James, Reynold
Abstract: An earlier special issue of this journal (Vol. 25, Issue 21, 2014), focused on the use of the lean model in developed countries. The authors of the introductory article (Bamber, Stanton, Bartram and Ballardie, 2014, pp. 2881–2891) observed that lean in an employment relations-unionist paradigm is relatively an under researched area, despite several organizations attempting to introduce lean being unionized. Resultantly, two broad themes they identified for further research, included the relationship between lean and employee unions, and the involvement of unions in the implementation of lean. This article addresses these themes by paying attention to an actual case study of the attempts made by the Japanese automotive giant Toyota, to establish its customized lean model within its unionized Australian affiliate TMCA (Toyota Motor Corporation Australia), during the period 1959–2015. The findings suggest that there is an acrimonious relationship between lean and the unions – as evidenced by Australia's strong manufacturing unions that posed significant challenges to Toyota's efficacious implementation of lean practices – and concur with a few of the key reasons that informed the decision taken by the company's top management in 2014 to cease their Australian manufacturing operations by 2017.